2018
DOI: 10.3389/fpsyg.2018.02029
|View full text |Cite
|
Sign up to set email alerts
|

A Daily Diary Study on Sleep Quality and Procrastination at Work: The Moderating Role of Trait Self-Control

Abstract: Background: This daily diary study investigates the relation between sleep quality during the night and its effect on procrastination at work during the next workday. Previous research has shown that sleep quality is an important variable for work behavior at the daily level, including employee performance, safety, health, and attitudes, such as work engagement. Also, sleep quality has been found to be negatively related to next-day work procrastination. However, these studies did not address trait differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 54 publications
(88 reference statements)
1
34
0
1
Order By: Relevance
“…While this study, guided by the Procrastination-Health Model, postulated that procrastination might be a determinant of poor sleep. Some prior studies have, on the other hand, argued that the causal direction could be the opposite (van Eerde & Venus, 2018). Namely, sleep deprivation results in depleted self-control resources, which make the affected individuals more likely to procrastinate (KĂźhnel, Bledow, & Feuerhahn, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…While this study, guided by the Procrastination-Health Model, postulated that procrastination might be a determinant of poor sleep. Some prior studies have, on the other hand, argued that the causal direction could be the opposite (van Eerde & Venus, 2018). Namely, sleep deprivation results in depleted self-control resources, which make the affected individuals more likely to procrastinate (KĂźhnel, Bledow, & Feuerhahn, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, self-control as a volitional factor may have an inhibitory effect on procrastination behavior. Numerous studies showed that self-control negatively predicted procrastination ( Kuhnel et al, 2018 ; Przepiorka et al, 2019 ), and trait self-control interacted with sleep quality in impacting next-day work procrastination ( van Eerde and Venus, 2018 ). Studies have also confirmed that academic self-control negatively predicts academic procrastination ( Ariely and Wertenbroch, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies should employ more timely measures of sleep quality; for example, ecological momentary assessment, which is characterized by repeated measurements of how participants feel in real situations. Researchers could assess sleep quality on a daily basis by using a “sleep diary” approach, so that each morning the person rates his/her sleep quality on the night before ( Eerde and Venus, 2018 ). Second, the cross-sectional data were collected and correlation analyses were conducted, which means we cannot make causal inferences.…”
Section: Discussionmentioning
confidence: 99%